Profile of professionals of the Brazilian production sector of timber housing - De Araujo, Victor; Polanco, Cesar; Morales, Elen [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Gava, Maristela [UNESP]; Garcia, José (The Korean Society of Wood Science Technology, 2019)
On account of the lack of education of Brazilian worker, this paper analyzed the characteristics of those professionals working in the production sector of timber houses. A sectoral survey was carried out with respective entrepreneurs to investigate the available professionals (career and contract types), evaluate the demands of skilled workers, and indicate solutions to improve the quality of labor qualification. Similarly, over 65% of sampled producers presented both direct-hired and outsourced workforce. For such contract ways, Civil Engineers and Architects were the main careers. Carpenters, Civil Engineers and Architects experienced on timber were the main sectoral demands. Timber Engineers have good potentials of service for this sector. The creation of courses on timber products can emerge as a key alternative to train people.
Keywords: Civil construction; Personal interview; Sectoral research; Wooden house